PENGARUH PENERAPAN PENDEKATAN JAS TERHADAP PENGUASAAN KETERAMPILAN PROSES SAINS SISWA SMA - Wahyuni, Furi Intan; Isnaeni, Wiwi; Marianti, Aditya (Journal of Biology Education, 2013)
The purpose of this research was to find out the application of Jelajah Alam Sekitar (JAS) Approach in teaching the digestive system for the studentâs science process skills at SMA N 12 semarang. This research was a Quasi Experimental Design research with Pre-test and Post-test of Non-equivalent Control Group Design which was for XI IPA 1 class as the experimental group and XI IPA 2 class as the control group. Method of choosing the sample was purposive sampling. The data were in the form of science process skills, learning result, studentsâ and teacherâs response. The analysis resulted in a correlation coefficient of 0.31Â and determination coefficient ofÂ 10%. The percentage of experimental classâ result was higher than control class (100% > 57%). 97% of the students responded well towards whereas the teacher gave positive response for the learning procedure. According to those results, it can be concluded that the application of Jelajah Alam Sekitar (JAS) in learning the digestive system had positive effect in the studentsâ mastery on science process skills.Â Penelitian ini bertujuan untuk mengetahui pengaruh penerapan pendekatan Jelajah Alam sekitar dalam pembelajaran materi sistem pencernaan terhadap penguasaan keterampilan proses sains siswa SMA N 12 Semarang. Penelitian ini merupakan penelitian Quasi eksperimental design dengan pola Pre and Post-test Non-equivalent Control Group Design dan diterapkan pada kelas XI IPA1 sebagai kelas eksperimen dan XI IPA2 sebagai kelas kontrol. Pengambilan sampel secara purposive sampling. Data berupa penguasaaan keterampilan proses sains, hasil belajar, tanggapan siswa, dan tanggapan guru. Hasil analisis menunjukkan harga koefisien korelasi sebesar 0,31 dan koefisisen determinasi sebesar 10%. Persentase hasil belajar kelas eksperimen > hasil belajar kelas kontrol (100% > 57%). Pembelajaran yang dilakukan ditanggapi baik oleh guru dan ditanggapi sangat baik oleh 97% siswa. Berdasarkan hasil, dapat disimpulkan bahwa penerapan pendekatan Jelajah Alam sekitar dalam pembelajaran materi sistem pencernaan berpengaruh positif terhadap penguasaan keterampilan proses sains siswa.